Evidence for temporal population replacement and the signature of ecological adaptation in a major Neotropical malaria vector in Amazonian Peru - Lainhart, William; Bickersmith, Sara A.; Nadler, Kyle J.; Moreno, Marta; Saavedra, Marlon P.; Chu, Virginia M.; Ribolla, Paulo Eduardo Martins [UNESP]; Vinetz, Joseph M.; Conn, Jan E. (BioMed Central, 2015)
The major Neotropical malaria vector, Anopheles darlingi, was reintroduced into the Iquitos, Loreto, Peru area during the early 1990s, where it displaced other anophelines and caused a major malaria epidemic. Since then, case numbers in Loreto have fluctuated, but annual increases have been reported since 2012. The population genetic structure of An. darlingi sampled before and after the introduction of long-lasting insecticidal nets (LLINs) was investigated to test the hypothesis of temporal population change (2006 vs. 2012). Current samples of An. darlingi were used to test the hypothesis of ecological adaptation to human modified (highway) compared with wild (riverine) habitat, linked to forest cover. In total, 693 An. darlingi from nine localities in Loreto, Peru area were genotyped using 13 microsatellite loci. To test the hypothesis of habitat differentiation in An. darlingi biting time patterns, HBR and EIR, four collections of An. darlingi from five localities (two riverine and three highway) were analysed. Analyses of microsatellite loci from seven (2006) and nine settlements (2012-2014) in the Iquitos area detected two distinctive populations with little overlap, although it is unclear whether this population replacement event is associated with LLIN distribution or climate. Within the 2012-2014 population two admixed subpopulations, A and B, were differentiated by habitat, with B significantly overrepresented in highway, and both in near-equal proportions in riverine. Both subpopulations had a signature of expansion and there was moderate genetic differentiation between them. Habitat and forest cover level had significant effects on HBR, such that Plasmodium transmission risk, as measured by EIR, in peridomestic riverine settlements was threefold higher than in peridomestic highway settlements. HBR was directly associated with available host biomass rather than forest cover. A population replacement event occurred between 2006 and 2012-2014, concurrently with LLIN distribution and a moderate El Niño event, and prior to an increase in malaria incidence. The likely drivers of this replacement cannot be determined with current data. The present-day An. darlingi population is composed of two highly admixed subpopulations, which appear to be in an early stage of differentiation, triggered by anthropogenic alterations to local habitat.
Keywords: Population replacement; Ecological adaptation; Anopheles darlingi; Malaria; Human biting rate; Microsatellites